The therapeutic effect of antidisbiotic means on the mucous sheath of rats digestive tract, obtaining peroxidized sunflower oil - Levitsky, A. P.; Gozhenko, A. I.; Bocharov, A. V.; Boris, G. Z.; Pustovoit, P. I.; Varava, G. N. (Journal of Education, Health and Sport, 2017)
Aim: Determine the therapeutic effect of antidysbiosis agents (ADA) on the condition of the mucous membrane of the digestive tract when consumed per-oxidized sunflower oil (PSO). Materials and Methods: Rats were fed 4 g / kg of PSO for 75 days. From the 31st day, they were administered one of the following ADA with 300 mg / kg of food: kvertulin (quercetin + inulin + calcium citrate), lekvin (lecithin + kvertulin) and lysozyme-forte (lysozyme + quercetin + inulin + gelatin + calcium citrate). The activity of elastase, urease, lysozyme, catalase and the content of MDA were determined in the homogenates of the mucous cheeks, small and large intestine. The ratio of catalase activity and the content of MDA was calculated by the API index, and the ratio of the relative activities of urease and lysozyme - the degree of dysbiosis. Results: The consumption of PSO in rats in the mucous membranes of the digestive tract increases the activity of elastase, urease, MDA content and the degree of dysbiosis while reducing the activity of lysozyme, catalase and the API index. In rats treated with ADA, the activity of elastase, urease, MDA content, and the degree of dysbiosis decrease, but the activity of lysozyme and catalase increase. Conclusion: Peroxide intoxication causes the development of mucositis, which can be prevented by antidysbiosis agents.